Pengaruh Zakat, Infaq, Shadaqah (ZIS) dan Indikator Ekonomi Makro Terhadap Tingkat Kemiskinan di Provinsi Aceh Tahun 2018-2020 - Hanifah Khusnul Karimah; Siti Aisyah (ITB AAS INDONESIA Surakarta, 2023)
Poverty is still an ever-present challenge in the development of Indonesia’s economy, therefore the government continues to strive to reduce absolute poverty and inequality. This study aims to examine and analyze the effect of Zakat, Infaq, Sadaqah (ZIS), economic growth, open unemployment and the Human Development Index (HDI) on the poverty rate in Aceh Province in 2018-2020. This study uses panel data regression analysis techniques. Based on testing, the best Fixed Effect Model (FEM) model is obtained. The estimation results show that economic growth has a significant and positive effect on poverty rate, and HDI has a significant and negative effect on poverty rate. While ZIS and open unemployment have no significant effect on poverty. Sufficient and high economic growth must be maintained since apart from being a measure of the success or decline of a region's development, it is also an indicator of people's welfare. Opportunities to increase employment must be continued by providing various kinds of training to the community and labour pool, to reduce the open unemployment rate